Clinical and pathological aspects of gossypiboma in a dog: Case report - Oliveira, R. [UNESP]; Matsui, A. [UNESP]; Ribeiro, J. O. [UNESP]; Simionato, G. [UNESP]; Simamura, A. C. [UNESP]; Canola, J. [UNESP]; Camplesi, A. [UNESP]; Vasconcelos, R. O. [UNESP]; Moraes, P. C. [UNESP] (FapUNIFESP (SciELO), 2019)
A female dog was treated at the Veterinary Hospital Governador Laudo Natel for symptomscaused by an intra-abdominal gossypiboma (gossypium: cotton; boma: place of hiding). Showing high morbidity and mortality, the gossypiboma is a granulomatous reaction that is formed in response to exposure to a textile matrix. The objective of this report is to describe the clinical and pathological findings of an intra-abdominal gossypiboma in a female dog. This patient arrived at urgent care showing increased abdominal volume, pain, and cachexia. Ultrasonography showed a regular contour formation that could not be completely delimited. The patient underwent exploratory laparotomy and died in the postoperative period. The gossypiboma had a smooth, firm, and purple-gray exterior surface. Microscopy revealed a severe reaction of desmoplasia around the necrotic region, residual textile material, and adipose tissue. Negligence by veterinarians leading to this condition can result in patients' death as well as causing psychological damage to owners.

Uma cadela foi atendida no Hospital Veterinário Governador Laudo Natel, apresentando sinais clínicos oriundos de gossipiboma intra-abdominal (gossypium: algodão e boma: local de ocultação), tais como aumento de volume abdominal, regurgitação e caquexia. A ultrassonografia evidenciou formação de contorno regular que não podia ser totalmente delimitada. A paciente foi submetida à laparotomia exploratória e veio a óbito no período pós-operatório. O gossipiboma mostrou-se com superfície externa lisa, firme e roxo-acinzentada apresentando-se à microscopia como reação severa de desmoplasia ao redor de material necrótico, resíduos de material têxtil e do tecido adiposo. A negligência por parte dos médicos veterinários pode levar pacientes ao óbito, bem como trazer prejuízos psicológicos aos proprietários. Objetiva-se, com este relato, descrever os achados clínicos e patológicos de uma cadela que apresentou um gossipiboma intra-abdominal.
Keywords: Cirurgia; Inflammatory reaction; Legal medicine; Medicina legal; Reação inflamatória; Surgery; Textile